Children of the future preschool educator formation of skills on hygiene – as a pedagogical problem - Tadjibaeva Gavharoy Ismailovna (Genius Journals, 2022)
In the article, taking into account the specific features of the field of preschool education, the formation of the skills of the future preschool teacher on child hygiene - as a pedagogical problem, first consists in explaining the social nature of his profession.
Keywords: Preschool education; physiology; hygiene; first educator